Coumarin as a Surrogate for the Protection‐group‐free Synthesis of o‐Hydroxy Stilbenes: Hydrolysis‐Decarboxylation‐Heck Coupling Reactions in One Pot. Issue 19 (25th August 2022) - Andhare, Nitin H.; Equbal, Danish; Sinha, Arun K.
Abstract: The 2‐hydroxystyrylbenzene scaffold is found in various compounds that are widely applicable in medicinal chemistry as well as material chemistry. Here, a successful attempt is made to develop a one‐pot protocol for the synthesis of 2‐hydroxystilbene derivatives via hydrolysis of natural coumarins followed by in situ decarboxylative Heck coupling with haloarenes. Fine tuning of the reaction conditions allowed exclusive formation of 2‐hydroxystyrylbenzenes over other possible side products, i. e., benzofuran/substituted coumarins. Abstract : An efficient, waste‐free, step‐economic protocol for the synthesis of 2‐hydroxystilbenes in one pot from a readily available natural substrate (i. e., coumarin) has been developed.